Evaluasi Efek Samping Vaksin Covid-19 di kalangan Staf dan Mahasiswa Universitas Misurata di Libya - Saad Aboualkasem; Salem Ebraiek; Mohamed Elwash; Fatma Altarhouni; Fatima Alzarrouk (Biota, 2022)
After a year of COVID-19 being distributed in all countries worldwide, several COVID-19 vaccines were invented by different companies. All of these vaccines got emergency approval from WHO because of critical conditions to fight this pandemic, but still, scientists work on clinical experiments to approve the safety of these vaccines and their adverse effects. This research tried to check the safety of vaccines imported from the Libyan Health Ministry. The comparison was among Sinovak, Sinopharm, AstraZeneka, Sputnik V, and Pfizer- BioNTech vaccines. The research aimed to compare the side effects of each vaccine after 24 hours of vaccination, this information was collected from people who work or study at Misurata University. The first notice of survey results was the small number of people who took the second dose of all vaccines, even if all second doses have been provided by the health ministry with the exception of sputnik V. Most side effects were clear in sputnik V, AstraZeneka, and Pfizer- BioNTech, on the other hand, Sinopharm and Sinovac were mostly with little side effects although some people had headache and fever. This research recommends for more action forward campaign that aims to convince Libyan people to get COVID-19 vaccines.